Significance of IgG-Avidity in Antenatal Rubella Diagnosis. - Olajide Olubunmi Agbede; Oluwapelumi Olufemi Adeyemi; Abdul Wahab Olanrewaju Olatinwo (Tehran University of Medical Sciences, 2013)
Objective: A descriptive study was carried out to determine the significance of IgG-affinity in the serological diagnosis of rubella infections in pregnancy. Materials and methods: A total of 92 pregnant women who had never received antirubella vaccines were recruited by simple random selection and did not exceed 24 weeks of gestation were recruited from the antenatal clinics of the University of Ilorin Teaching Hospital. Rubella virus-specific IgG, IgG-affinity and IgM were tested, using the Indirect ELISA methods. Results:IgG-Affinity tests showed that 2 (2.2%) out of the 92 pregnant women, who were in their first and second trimester pregnancies respectively, had primary Rubella infections, while 1 (1.1%) primigravidae had a re-infection with rubella virus. It was also discovered that out of the 13 multigravid subjects that reported to have lost previous pregnancies, 2 (15.4%) cases may have been due to rubella infections that occurred during organogenesis. Conclusion: Although the isolation of the whole virus or the viral nucleic material is the best basis for diagnosis, IgG-affinity is a proven supplementary serological diagnosis, to distinguish reinfection or viral persistence from primary exposure for prompt and accurate diagnosis. This is necessary for proper counselling of pregnant women especially in low economies where molecular diagnosis may not be affordable.